A double blind, randomized, placebo controlled trial of the efficacy, quality of life and safety of food allergen‐specific sublingual immunotherapy in client owned dogs with adverse food reactions: a small pilot study. Issue 5 (18th July 2016) - Maina, Elisa; Cox, Eric
Abstract : Background: Food allergen‐specific sublingual immunotherapy (FA‐SLIT) has emerged as a novel and successful approach for desensitizing human patients to specific food allergens. It has not been tested in dogs. Objective: To investigate the efficacy, quality of life (QoL), tolerability and safety of FA‐SLIT in dogs with adverse food reactions (AFR). Methods: Dogs with proven AFR were randomized to treatment (T group; n  = 7) or placebo (P group; n  = 6) to receive either FA‐SLIT (based on the results of a food elimination trial) or glycerinated saline, respectively. The treatment was continued daily for 6 months with fortnightly dosage escalations. To evaluate the treatment, pruritus Visual Analog Scale (pVAS), Canine Atopic Dermatitis Extent and Severity Index (CADESI‐04), QoL, faecal consistency scores, owner assessment, overall tolerability scores and blood analyses were assessed. Results: Eleven dogs completed the study, two dogs in the T group were withdrawn by the owner after FA‐SLIT exacerbated clinical signs of AFR. Statistical tests showed significant protection against food challenge induced clinical signs following FA‐SLIT therapy, as indicated by reduced pVAS and CADESI scores ( P  <   0.05). The QoL did not differ between groups. The treatment was rated as effective or quite effective by 80% of the owners, whereas placebo was rated as ineffective by all owners. Conclusions and clinical importance: FA‐SLIT was effective, well tolerated and safe. No severe adverse events were recorded; erythema and pruritus were reported in association with only 0.7% of the dispensed doses. Larger clinical trials with more extended maintenance immunotherapy periods will be needed to provide more precise estimates of efficacy and frequency of adverse events. Abstract : Background ‐ Food allergen‐specific sublingual immunotherapy (FA‐SLIT) has emerged as a novel and successful approach for desensitizing human patients to specific food allergens. It has not been tested in dogs. Objective ‐ To investigate the efficacy, quality of life (QoL), tolerability and safety of FA‐SLIT in dogs with adverse food reactions (AFR). Conclusions and clinical importance ‐ FA‐SLIT was effective, well tolerated and safe. No severe adverse events were recorded; erythema and pruritus were reported in association with only 0.7% of the dispensed doses. Larger clinical trials with more extended maintenance immunotherapy periods will be needed to provide more precise estimates of efficacy and frequency of adverse events. Résumé: Contexte: L'immunothérapie spécifique d'allergènes alimentaires sublinguale (FA‐SLIT) se développe comme une nouvelle approche de désensibilisation chez l'homme pour des allergènes alimentaires spécifiques. Aucun test n'a été réalisé chez le chien. Objectif: Etudier l'efficacité, la qualité de vie (QoL), la tolérance et l'innocuité de FA‐SLIT chez des chiens avec des réactions alimentaires indésirables (AFR). Méthodes: Des chiens atteints d'AFR ont été randomisés au groupe traitement (groupe T; n=7) ou groupe placebo (groupe P; n=6) pour recevoir respectivement, soit FA‐SLIT basé sur les résultats d'un régime d'éviction soit de la solution saline. Le traitement a été poursuivi une fois par jour pendant 6 mois avec augmentation des doses toutes les deux semaines. Afin d'évaluer le traitement, la pVAS (échelle visuelle analogue de prurit), le CADESI‐04 (Canine Atopic Dermatitis Extent and Severity Index), la QoL, les scores de consistance fécale, l'évaluation des propriétaires, les scores de tolérance globale et les analyses sanguines ont été mesurées. Résultats: Onze chiens ont été inclus dans l'étude, deux chiens dans le groupe T ont été exclus par le propriétaire après exacerbation des signes cliniques d'AFR par FA‐SLIT. Les tests statistiques ont montré une protection significative contre les signes cliniques induits par les provocations alimentaires à la suite de FA‐SLIT comme indiqué par une pVAS et des scores CADESI diminués ( P  <0.05). La QoL de différait pas entre les groupes. Le traitement a été estimé efficace ou assez efficace par 80% des propriétaires tandis que le placebo a été évalué inefficace par tous les propriétaires. Conclusions et importance clinique: La FA‐SLIT était efficace, bien tolérée et sure. Aucun effet indésirable sévère n'a été enregistré; érythème et prurit ont été rapporté en association avec seulement 0, 7%des doses dispensées. Des études cliniques plus larges avec une période d'immunothérapie de maintenance plus longue sont nécessaires afin de fournir des estimations plus précises d'efficacité et de fréquence d'effets secondaires. Resumen: Introducción: La inmunoterapia sublingual con alérgenos específicos de alimentos (FA‐SLIT) ha surgido como un nuevo y exitoso método para desensibilizar a pacientes humanos frente a alérgenos alimentarios específicos. No se ha probado en perros. Objetivo: Investigar la eficacia, la calidad de vida (QoL), la tolerabilidad y la seguridad de FA‐SLIT en perros con reacciones adversas a alimentos (AFR). Métodos: Perros con AFR probada fueron asignados aleatoriamente a grupo de tratamiento (grupo T; n = 7) o placebo (grupo P; n = 6) para recibir ya sea FA‐SLIT (basado en los resultados de un ensayo de eliminación de alimentos) o solución salina glicerinada, respectivamente. El tratamiento se continuó diariamente durante 6 meses con incrementos escalonados de dosis quincenales. Para evaluar el tratamiento se valoraron el prurito con Escala Analógica Visual (pVAS), el índice de extensión y severidad de la dermatitis atópica canina (CADESI‐04), QoL, el índice de consistencia fecal, la evaluación del propietario, valores de tolerabilidad general y análisis de sangre. Resultados: Once perros completaron el estudio, dos perros en el grupo T fueron retirados por el propietario después de que la FA‐SLIT exacerbara los signos clínicos de AFR. Las pruebas estadísticas mostraron una protección significativa contra los signos clínicos tras la reexposición a alimentos después de la terapia FA‐SLIT, según lo indicado por los valores reducidos de pVAS y CADESI ( P <0, 05). La QoL no difirió entre los grupos. El tratamiento fue calificado como eficaz o muy eficaz en un 80% de los propietarios, mientras que el placebo fue calificado como ineficaz por todos los propietarios. Conclusiones e importancia clínica: FA‐SLIT fue eficaz, bien tolerada y segura. No hubo eventos adversos graves; eritema y prurito fueron descrito en asociación con el tratamiento en sólo el 0, 7% de las dosis administradas. Se necesitan ensayos clínicos más amplios con períodos más extendidos de inmunoterapia de mantenimiento para proporcionar estimaciones más precisas de la eficacia y la frecuencia de eventos adversos. Zusammenfassung: Hintergrund: Eine Futterallergen‐spezifische sublinguale Immuntherapie (FA‐SLIT) stellt sich als neue erfolgreiche Methode dar, um Menschen gegen spezifische Futterallergene zu desensibilisieren. Es wurde bisher bei Hunden nicht getestet. Ziele: Eine Untersuchung der Wirksamkeit, der Lebensqualität (QoL), der Toleranz und Sicherheit von FA‐SLIT bei Hunden mit Nebenwirkungen auf Futter (AFR). Methoden: Hunde mit einer bestätigten AFR wurden zufällig in Gruppen eingeteilt (T Gruppe; n =7) oder Plazebo (P Gruppe; n =6), um entweder FA‐SLIT (basierend auf einer Ausschlussdiät) beziehungsweise glyzerinisierte Kochsalzlösung zu erhalten. Die Behandlung wurde täglich 6 Monate lang mit einer Dosiserhöhung alle 14 Tage durchgeführt. Um die Behandlung zu beurteilen wurden Visual Analog Scale (pVAS), Canine Atopic Dermatitis Extent and Severity Index (CADESI‐04), QoL, Kotkonsistenzen, Besitzerbeurteilung, allgemeine Toleranzwerte und Blutuntersuchungen angewendet bzw durchgeführt. Ergebnisse: Elf Hunde beendeten die Studie, zwei Hunde der Gruppe T wurden von den Besitzern aus der Studie genommen, nachdem die FA‐SLIT die klinischen Anzeichen der AFR verstärkte. Statistische Untersuchungen zeigten einen signifikanten Schutz gegenüber den durch die Futterprovokation induzierten klinischen Anzeichen, die der FA‐SLIT Therapie folgten, was durch einen reduzierten pVAS und CADESI Score (P<0, 05) deutlich wurde. Die QoL war in den beiden Gruppen nicht verschieden. Die Behandlung wurde von 80% der BesitzerInnen als effektiv oder ziemlich effektiv eingestuft, während Plazebo von allen BesitzerInnen als unwirksam eingestuft wurde. Schlussfolgerungen und klinische Bedeutung: Die FA‐SLIT war wirksam, wurde gut toleriert und war sicher. Es wurden keinen starken Nebenwirkungen beschrieben; Erythem und Juckreiz wurden nur bei 0, 7% der verabreichten Dosierungen beschrieben. Größere klinische Studien mit einer weitreichenderen Immuntherapie als Erhaltungstherapie sind nötig, um genauere Schätzungen der Wirksamkeit und Frequenz von Nebenwirkungen zu ermöglichen. 要約: 背景: 食物アレルゲン特異的舌下免疫療法(FA‐SLIT)は、ヒトの患者で特定の食物アレルゲンに対して減感作するための新しい成功し得るアプローチとして期待されている。イヌにおいては、この治療法は試されていない。 目的: 食物有害反応(AFR)のイヌにおけるFA‐SLITの効果、生活の質(QoL)、寛容性および安全性を調査すること。 方法: AFRが明らかになったイヌを、FA‐SLIT(除去食試験の結果に基づいて)あるいはグリセリン生理食塩水のいずれかを投与する治療群(Tグループ; n =7)あるいはプラセボ群(Pグループ; n =6)にランダムに割りつけた。治療は1日1回6ヶ月にわたって続けられ、2週間ごとに用量を増加させた。治療を評価するために、掻痒ビジュアルアナログスケール(pVAS)、Canine Atopic Dermatitis Extent and Severity Index (CADESI‐04)、QoL、糞便の硬さのスコア、飼い主の評価、全体的な寛容性スコアおよび血液分析を評価した。 結果: 11頭のイヌが試験を完了し、Tグループの2頭のイヌはFA‐SLITによりAFRの臨床症状が悪化したため、飼い主の希望により脱落した。統計学的な検査ではpVASとCADESIスコアの減少が示されたことによって( P < 0.05)FA‐SLIT療法後に食物暴露誘発臨床症状に対して有意に予防できることが示された。QoLは2つのグループで差は無かった。治療群は飼い主の80%が効果的あるいはかなり効果的と判定したが、プラセボ群はすべての飼い主が効果なしと判定した。 結論および臨床的な重要性: FA‐SLITは効果的で、よく寛容され安全である。重篤な有害事象は報告されなかったが、紅斑および掻痒は投与群で、0.7%のみで関連が報告された。より長期間の維持免疫療法を設けたより大型の臨床治験が、より最適な効果の判定や有害事象の頻度を述べるためには必要とされる。 摘要: 背景: 特异性食物过敏原舌下免疫疗法(FA‐SLIT)是一种新方法, 并且已成功降低人对特异性食物过敏原的敏感性。但仍未在犬上尝试。 目的: 调查食物副反应(AFR)患犬使用FA‐SLIT的有效性、生活质量(QoL)、耐受性和安全性。 方法: 将已确诊具有AFR的患犬随机进行分组, 一组接受FA‐SLIT(基于食物排除试验的结果)治疗(T组; n = 7), 另一组作为对照组(P组; n = 6)给予甘油酸盐。该治疗持续6个月, 并且每两周增加剂量。评估治疗方案、瘙痒直观类比标度(pVAS)、犬异位性皮炎程度和严重性指数(CADESI‐04)、QoL、粪便稳定性指数、动物主人评估、整体耐受分数和血液分析结果。 结果: 11只犬完成该项研究, T组中2只犬由于FA‐SLIT后AFR症状加重, 动物主人自行停止FA‐SLIT。统计学检查发现, 接受FA‐SLIT治疗后, 对于食物随机产生的临床症状有很好的预防作用, pVAS和CADESI分数有所下降( P <0.05)。两组犬的生活质量没有不同。80%动物主人评估该治疗有效或非常有效, 然而所有动物主人反应安慰剂无效。 总结和临床意义: FA‐SLIT有效、耐受性良好且安全。无严重不良反应记录;据报道, 推荐剂量下仅有0.7%出现红斑和瘙痒。目前, 仍需要大规模的临床试验, 以及更长期的免疫治疗, 进而对有效性和不良反应出现的频率进行更精确的评估。 Resumo: Contexto: Imunoterapia sublingual trofoalérgeno‐específica (FA‐SLIT) tem emergido como uma nova e bem sucedida abordagem para dessensibilização de pacientes humanos a alérgenos alimentares específicos. FA‐SLIT ainda não foi testada em cães. Objetivos: Investigar a eficácia, qualidade de vida (QoL), tolerabilidade e eficácia de FA‐SLIT em cães com reações adversas a alimentos (AFR). Métodos: Cães com AFR comprovada foram randomizados em tratamento (grupo T, n = 7) ou placebo (grupo P, n = 6) para receber FA‐SLIT (baseada em resultados da dieta de eliminação) ou salina glicerinada, respectivamente. O tratamento foi continuado diariamente por seis meses com aumento na dose a cada duas semanas. Para avaliar o tratamento, foram realizados escala visual analógica de prurido (pVAS), Canine Atopic Dermatitis Extent and Severity Index (CADESI‐04), QoL, escore de consistência das fezes, avaliação do proprietário, escores de tolerabilidade geral e análises hematológicas. Resultados: Onze cães concluíram o estudo, dois cães do grupo T foram retirados do experimento pelos proprietários após FA‐SLIT exacerbar os sinais clínicos da AFR. Provas estatísticas demonstraram proteção significativa contra sinais clínicos induzidos por desafio alimentar, seguidos por administração de FA‐SLIT, como indicado pela redução dos escores de pVAS e CADESI‐04 ( p < 0, 05). Não houve diferença entre o QoL nos dois grupos. O tratamento foi classificado como eficaz ou bastante eficaz por 80% dos proprietários, enquanto o placebo foi classificado como ineficaz por todos os proprietários. Conclusões e importância clínica: FA‐SLIT se mostrou eficaz, bem tolerada e segura. Nenhuma reação adversa grave foi reportada. Eritema e prurido foram associados a apenas 0, 7% das doses administradas. Ensaios clínicos maiores e com períodos de imunoterapia mais longos serão necessários para fornecer estimativas de eficácia e frequência de reações adversas mais precisas.